Morphological Study of Parathyroid in Relation to Thyroid Gland of Bangladeshi People - Sultana, SZ; Mannan, S; Sultana, S; Khan, MK; Rahman, MH; Hossain, A; Khalil, M; Khalil, M (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):137-42The abstract of this article is available on the PubMed website